Manpower policy in the United Kingdom - Organisation for Economic Co-operation and Development (Paris : O.E.C.D. ; London : H.M.S.O., 1970)
reports have been for Sweden (1964), United States (1964), Greece (1965), Canada (1966), Austria (1967), and the Netherlands (1967). The United Kingdom report consists of three parts: a factual survey by U. K. specialists of the labor market and of manpower policies, as of October 1968, in the This study is the seventh in the series of the OECD reviews of manpower and social policies in different member countries. Previous reports have been for Sweden (1964), United States (1964), Greece (1965), Canada (1966), Austria (1967), and the Netherlands (1967). The United Kingdom report consists of three parts: a factual survey by U. K. specialists of the labor market and of manpower policies, as of October 1968, in the United Kingdom; an examiners' report on that survey, which includes an assessment of the practical impact of the policies; and a lengthy conclusion prepared by the OECD Committee on Manpower and Social Affairs. The Report aims to examine various policies in order to identify particular techniques or programs of interest to other countries or, where possible in the case of any member country, to point out alternative ways of attaining manpower goals.
Includes bibliographical references.
rpm 15/03/2018
Loans
Keywords: Manpower policy